Molecular Docking And In Vitro Studies Of New Quinoline Derivatives With Antimalarial Potential (International Journal of Environmental Sciences, 2025)
Malaria remains a critical global health issue, especially in tropical and subtropical regions, due to increasing resistance to existing antimalarial drugs. Quinoline-based compounds, such as chloroquine, have shown historical efficacy, but the emergence of resistant Plasmodium strains necessitates the development of novel analogs. In this study, a series of newly synthesized quinoline derivatives were evaluated for their antimalarial potential through both molecular docking and in vitro assays. Molecular docking studies were conducted to assess binding affinity and interaction modes of the compounds with key Plasmodium falciparum targets, including dihydrofolate reductase (PfDHFR) and heme detoxification pathway components. Promising candidates were then subjected to in vitro testing against chloroquine-sensitive (3D7) and chloroquine-resistant (W2) P. falciparum strains. Several derivatives exhibited potent activity, with IC₅₀ values in the low micromolar range and favorable selectivity indices. The structure-activity relationship (SAR) analysis revealed critical functional groups contributing to antimalarial efficacy. These findings suggest that the new quinoline derivatives are promising leads for the development of next-generation antimalarial agents.